IMAGE SECURITY USING INTRA-FILE SECURITY - Abdulla, Sura (Iraqi Journal of Science, 2024)
Typical image cryptographic systems provide security by encrypting entire image. This has the advantage of simplicity, but does not allow for fine-grained protection of data within very large image files, which is very important in some applications where some but not all the image is sensitive or classified.In this paper, a new method is proposed for securing parts of the image (i.e. sensitive information). The proposed method combines the Intra-File security, image inpainting and cryptography techniques to secure the sensitive parts of an image and leave the rest of the image without any changes, further more, it allows multiple levels of security for the same image without the need to have more than one copy of that image. Experimental results of the proposed method provides better security than the classical methods.